Recent advancements in aquaponics with special emphasis on its sustainability - Chythra Somanathan Nair; Ramya Manoharan; Drishya Nishanth; Radhakrishnan Subramanian; Elke Neumann; Abdul Jaleel (Journal of the World Aquaculture Society)
Abstract An aquaponic system which is an integration of hydroponics with aquaculture is sustainable, ecologically friendly, and uses non‐renewable resources with very high efficacy. The increasing trend in aquaponics research demonstrates a growing recognition of its potential to address critical global issues such as food security, water conservation, and sustainable agriculture, particularly in regions vulnerable to climate change and resource limitations. It has witnessed remarkable advancements in recent years, with various methods and variations emerging to enhance its functionality and productivity. The purpose of this review is to unify fragmented research on aquaponics and provide a comprehensive resource that emphasizes its potential for broad adoption and successful implementation in varied environments. This review focuses on recent innovations in aquaponic system designs for various climates and examines key advancements in critical areas, including microbial communities, biofiltration, feed management, water quality, and nutrient cycling, emphasizing the interdisciplinary nature of aquaponics. Coupled systems suit moderate climates with high resource efficiency, while decoupled systems offer flexibility across diverse climates by allowing independent control of each component. Innovations such as sandponics, algaeponics, and saline aquaponics address challenges like water scarcity and nutrient efficiency. Smart technologies like IoT and AI are integrated into aquaponics, automating monitoring and nutrient management for better productivity. Emerging areas, including vermi‐aquaponics and flocponics, offer new solutions for nutrient cycling, making aquaponics more efficient, adaptable, and resource‐conserving globally. This paper also examines the sustainability aspects of aquaponics, emphasizing its economic, social, and environmental dimensions. Despite high setup costs and nutrient complexities, aquaponics offers significant potential for sustainable food production by minimizing water use and reducing synthetic fertilizers. Its scalability in both urban and rural areas, along with innovations like vertical systems, presents promising solutions for enhancing agriculture and food security across diverse environments.